Lipoedema and Pain: What is the role of the psyche? – Results of a pilot study with 150 patients with Lipoedema - Erbacher, Gabriele; Bertsch, Tobias (Phlebologie, 2020)
Introduction The present exploratory study is the first so far to investigate the psychological stress in the period before the development of pain symptoms typical for lipoedema.Methods 150 patients diagnosed with lipoedema syndrome were questioned in semi-structured interviews about psychological stress and were diagnosed with psychological disorders according to ICD-10 criteria. The development of the symptoms typical for lipoedema was recorded in a second interview. Both interviews were blended together in collaboration with the patients, this means Lipoedema-associated pain and psychological stress were related to time.Result Exactly 80 % of the patients diagnosed with lipedema show a high level of psychological distress immediately before the onset of lipedema-associated symptoms! In this study, mental distress was defined as the presence of a manifest mental disorder (ICD 10 F diagnosis) such as Depression, eating disorder or post-traumatic stress disorder and/or serious psychological distress such as burnout syndrome or chronic stress.Summary These results contradict a widespread statement that all psychological problems of patients with the diagnosis lipoedema syndrome are caused solely by lipoedema, that lipoedema even causes the patient’s mental disorder.Moreover, depression and posttraumatic stress disorders are significantly related to the maximum pain intensity estimated by patients in everyday life. This demonstrates that it is imperative to rethink lipoedema therapy and to implement a psychosocial pillar in an overall therapy concept.Einleitung Die vorliegende explorative Studie ist die bislang erste, in der die psychische Belastung im Zeitraum vor Auftreten der Lipödem-assoziierten Schmerzsymptomatik erforscht wird.Methode 150 Patientinnen mit Lipödem-Syndrom wurden in halbstrukturierten Interviews zu psychischen Belastungen befragt und zu psychischen Störungsbildern nach ICD-10-Kriterien diagnostiziert. In einem zweiten Interviewstrang wurde die Entwicklung der Lipödem-typischen Beschwerden erhoben. Im Anschluss erfolgte gemeinsam mit den Patientinnen das Überblenden beider Interviewbereiche, d. h. Lipödem-assoziierte Schmerzen und psychische Belastungen wurden in einen zeitlichen Zusammenhang gesetzt.Ergebnis Exakt 80 % der Patientinnen mit der Diagnose Lipödem zeigten eine hohe psychische Belastung unmittelbar im Zeitraum vor der Entstehung Lipödem-assoziierter Beschwerden! Psychische Belastung wurde in dieser Studie definiert als das Vorliegen einer manifesten psychischen Störung (ICD-10-F-Diagnose), wie z. B. Depression, Essstörung oder posttraumatische Belastungsstörung, oder/und gravierende psychische Auffälligkeit, wie z. B. Burnout-Syndrom oder chronischer Stress.Zusammenfassung Die Ergebnisse widersprechen damit einem weit verbreiteten Statement, dass alle psychischen Probleme von Patientinnen mit der Diagnose Lipödem-Syndrom ausschließlich durch das Lipödem bedingt seien, ein Lipödem sogar psychisch krank mache.Depression und Traumafolgestörungen stehen darüber hinaus in signifikantem Zusammenhang mit den von den Patientinnen eingeschätzten maximalen Schmerzstärken im Alltag. Dies macht deutlich, dass die Therapie für Patientinnen mit der Diagnose Lipödem neu gedacht werden und die psychosoziale Säule zwingend in einem Gesamttherapiekonzept verankert werden muss.
Keywords: lipoedema; mental stress; mental disease; pain; scientific evidence